POTRET MOTIVASI PADA SYIIR ‘IBAADAALLAH RIJAALALLAH DALAM KITAB MANAQIB NURUL BURHANI: STUDI SEMIOTIKA RIFFATERRE - A. Nawawi Alfan Afifi (Fakultas Syariah dan Adab Universitas Nahdlatul Ulama Sunan Giri, 2023)
Reading literary works is also related to concretization which allows for different results to be obtained from differences in time and the social influences that surround them. Differences in the results of readers' interpretations are also due to the broad scope of meaning in a literary text. In analyzing the object of literary works, the writer chooses Syiir Ibaadallah Rijalallah which is contained in the book Manaqib Nurul Burhani. The meaning of poetry in this article uses semiotic tools with the method of searching for meaning according to what Riffatre directs. contains motivation to increase enthusiasm for life and increase self-development through being active and innovative. . Indirectly it will bring out privileges to oneself and indirectly benefits will arise both individually and collectively.